Blue Electrofluorescence Resulting from Exergonic Harvesting of Triplet Excitons. Issue 18 (11th June 2019) - Yi, Seung Yeon; Ihn, Soo‐Ghang; Sim, Myungsun; Kim, Jong Soo; Kim, Inkoo; Chung, Yeon Sook; Huh, Dal Ho; Kim, Sunghan; You, Youngmin
Abstract: Advances in electroluminescence demand the development of emissive molecules capable of utilizing all of the electrogenerated excitons. Here, a molecular strategy to harvest the excitons without relying on late transition metals or thermal activation is designed and evaluated. The key process deployed is an exergonic, El‐Sayed rule‐allowed reverse intersystem crossing (ES‐rISC) from the triplet n–π * transition state to the singlet π–π * transition state, followed by fluorescent decay of the latter. To demonstrate the strategy, a series of fluorescent molecules consisting of a 9, 10‐diphenylanthracene core and different carbonyl n–π * units (SY compounds) is created. The compounds display a strong blue fluorescence emission with high photoluminescence quantum yields of up to 0.93. Multilayer organic electroluminescence devices containing the SY compounds exhibit maximum external quantum efficiencies greater than that obtained from a singlet‐exciton‐only control device. This improvement is due to their capacity to utilize triplet excitons for fluorescence emission. The studies demonstrate that exergonic ES‐rISC can serve as a promising pathway for creating inexpensive and tractable organic dopants for high‐efficiency electroluminescence. Abstract : Triplet‐exciton harvest by exergonic, El‐Sayed rule‐allowed reverse intersystem crossing is demonstrated for blue electroluminescence. The effectiveness of this exciton‐harvesting strategy is shown by synthesis of a novel series of systematically controlled fluorescent molecules.